Pengaruh Permainan Kooperatif Terhadap Peningkatan Interaksi Sosial Anak Usia 5-6 Tahun di TK Pembina HKBP Tarutung - Agus Niada Lawolo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of cooperative games on improving social interaction among 5-6 year old children at the Pembina HKBP Tarutung Kindergarten. The research hypothesis was: